Reflections on return to sport - Desmond, R. A. (The University of Western Ontario, 2021)
The COVID-19 pandemic has presented community sport organizations with many complex challenges, but also unique opportunities to reflect and rethink their practices (Fullagar, 2020). This study presents an autoethnography of my experiences working as a Technical Leader for a community sport organization (CSO) throughout the COVID-19 pandemic. The research questions were: 1) What were the features of organizational capacity that were most important to the CSO`s effectiveness, survival and resilience during the pandemic? and 2) What were the capacity features that were most impactful to my own ability to carry out my role effectively within the club? Through the autoethnographic process, I observed leader dedication, redundancy, dedicated staff, shared values and open communication to be essential features of organizational capacity and resilience during the pandemic. I also observed environmental instability, failures to retain staff and conflict to limit the club`s ability to be effective during return to play, and my own effectiveness within my role. Through sharing my experiences, community sport organizations may gain a greater understanding of the capacity features and necessary steps for efficient functioning and survival. Leaders and managers of CSOs may also gain valuable insight into how to effectively manage an organization through environmental uncertainty.